1993
DOI: 10.1128/jb.175.22.7500-7504.1993
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis reveals the importance of conserved charged residues for the transport activity of the PheP permease of Escherichia coli

Abstract: Site-directed mutagenesis has been used to identify a number of charged residues essential for the transport activity of the PheP protein. These residues are highly conserved in the cluster of amino acid transporters. However, some other conserved residues and a number of aromatic residues have been shown not to be essential for transport activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…In the case of PheP, the cytoplasmic loop between transmembrane spans VIII and IX has been shown to be very sensitive to single amino acid insertions and to contain two highly conserved amino acid residues, R317 and P341, each of which is critical for protein function (6,9). Since Hu and King have suggested that the role proposed for the CAR in GabP may also apply to all other members of the AAT family, we carried out a similar analysis of the putative SPS in PheP to test the generality of the results obtained with GabP (2).…”
mentioning
confidence: 99%
“…In the case of PheP, the cytoplasmic loop between transmembrane spans VIII and IX has been shown to be very sensitive to single amino acid insertions and to contain two highly conserved amino acid residues, R317 and P341, each of which is critical for protein function (6,9). Since Hu and King have suggested that the role proposed for the CAR in GabP may also apply to all other members of the AAT family, we carried out a similar analysis of the putative SPS in PheP to test the generality of the results obtained with GabP (2).…”
mentioning
confidence: 99%
“…AroP, together with the closely related phenylalanine-specific permease PheP, belongs to a superfamily of permeases involved in the transport of amino acids in bacteria and yeast (32,33).…”
mentioning
confidence: 99%
“…At the position corresponding to 118 in PheP, other bacterial members of the family contain either glutamate or aspartate. Converting glutamate 118 of the PheP protein to glycine, valine, leucine, tryptophan, or asparagine has been shown to completely destroy transport activity, whereas changing it to aspartate reduces transport activity to 36% of wild-type level (24). These results indicate the importance of glutamate 118, which is presumed to have a critical role either in proton translocation or in substrate binding or both.…”
Section: Discussionmentioning
confidence: 58%
“…Glutamate 118, whose possible function is discussed below, is a highly conserved residue whose replacement by residues other than aspartate leads to loss of function (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation